The start of a conversation on the value of New Zealand's natural capital - Sonette van Zyl; Joey Au (New Zealand Government, The Treasury, 2018)
Natural capital refers to all aspects of the natural environment. It includes individual assets such as minerals, energy resources, land, soil, water, trees, plants and wildlife. It also includes broader ecosystems and their services; that is, the joint functioning of, or interactions among, different environmental assets, as seen in forests, soil, aquatic environments and the atmosphere.
Keywords: 330